The Use Of Flashcard Media With Sign Language In Improving English Vocabulary Of Deaf Students In Grade VI At SD Negeri 2 Bengkala - Putu Rani Pratiwi; Made Hery Santosa; I Ketut Trika Adi Ana (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to investigate how the use of flashcards can improve the English vocabulary skills of sixth-grade students at SD Negeri 2 Bengkala. This study used a classroom action research (CAR) design that combines qualitative and quantitative methods. The subjects of the study consisted of two deaf students in sixth grade, while the object of the study was the use of flashcards in English learning. Data were collected through tests and observation checklists. The tests were used to measure students' vocabulary mastery, while the observation checklists were used to assess the increase in students' interest and attention during the learning process. The test results were analyzed quantitatively using descriptive statistics, while the qualitative data were analyzed using an interactive data analysis model. The results showed an increase in the English vocabulary mastery of deaf students with the use of flashcards. Based on the test results, the average post-test score in the first cycle was 65, which then increased in the second cycle to 87.5. This increase indicates that flashcards are effective in helping deaf students master English vocabulary. The observation results also supported these quantitative findings. In each cycle, deaf students increasingly showed greater interest and attention during the teaching and learning process. This improvement is due to the use of engaging images and games that create a more enjoyable classroom atmosphere. This improvement can also be attributed to more active interaction between students and teachers, which makes students feel more motivated to learn. Thus, the use of flashcards has been proven to improve deaf students' English vocabulary mastery and increase their interest and attention in learning. This research provides an important contribution to the development of more inclusive and enjoyable learning methods for deaf students and can serve as a reference for educators in designing effective and engaging learning.